Salinity Driven Selection and Local Adaptation in Baltic Sea Mytilid Mussels - Knöbel, Loreen; Nascimento-Schulze, Jennifer C.; Sanders, Trystan; Zeus, Dominique; Hiebenthal, Claas; Barboza, Francisco R.; Stuckas, Heiko; Melzner, Frank (Frontiers in Marine Science, 2021)
Baltic blue mussels can colonise and dominate habitats with far lower salinity (<10 psu) than other Mytilus congeners. Pervasive gene flow was observed between Western Baltic Mytilus edulis living at high salinity conditions and Eastern Baltic M. trossulus living at lower salinites, with highest admixture proportions within a genetic transition zone located at intermediate salinities (Darss Sill area). Yet, we do not understand the impacts of low salinity on larval performance, and how salinity may act as an early selective pressure during passive larval drift across salinity gradients. This study tested whether larvae originating from two different populations along the natural salinity cline in the Baltic Sea have highest fitness at their native salinities. Our results suggest that Eastern Baltic M. trossulus (Usedom, 7 psu) and Western Baltic M. edulis (Kiel, 16 psu) larvae display better performance (fitness components: growth, mortality, settlement success) when reared at their respective native salinities. This suggests that these populations are adapted to their local environment. Additionally, species diagnostic markers were used for genetic analyses of transition zone (Ahrenshoop, 11 psu) mussel larvae exposed to low salinity. This revealed that low salinity selection resulted in a shift towards allele frequencies more typical for Eastern Baltic M. trossulus. Thus, salinity acts as a selective pressure during the pre-settlement phase and can shape the genetic composition of Baltic mussel populations driving local adaptation to low salinity. Future climate change driven desalination, therefore, has the potential to shift the Baltic Sea hybrid gradient westward with consequences for benthic ecosystem structure.